The influence of work motivation and organizational cullture on the productivity of health workers at Pagar Jati Deliserdang Health Center - Naibaho, Togar; Naibaho, Winfrontstein (Institute of Computer Science (IOCS), 2025)
The purpose of this study was to determine the relationship between work motivation and organizational culture on the performance of the Pagarjati Health Center, Deliserdang Regency. To answer the research objectives, a study was conducted on all staff of the Pagarjati Health Center, totaling 112 people. The method used was descriptive analysis and structural equation model (SEM) analysis. Through the results of the study and analysis of work motivation and organizational culture, it was found that they had a significant effect on job satisfaction and had a significant effect. The implication of this study is to be able to improve the ability of a leader and the existing organizational culture, so that aspects of employee job satisfaction can be met, because in general high employee job satisfaction will be able to increase the work motivation of the Pagarjati Health Center staff, Deliserdang Regency.